Desenvolvimento de nanopartículas poliméricas de Eudragit® RL 100 contendo tioconazol para tratamento de doença fúngica ocular - Wolf, Jéssica Fernanda (2020)
The human eye, due to its unique structure and continuous exposure to the external environment, becomes susceptible to contamination by several pathogenic microorganisms, among which are fungi. In this way, the eye defence systems are affected, leading to the appearance of infections, such as fungal keratitis. Tioconazole is characterized by being an imidazole antifungal drug with a broad spectrum of action, a drug used in the treatment of vaginal fungal infections and dermatophytosis. However, it presents absorption problems, which may compromise its therapeutic action. Thus, nanotechnology emerges as an alternative, since these systems can provide an increase in therapeutic efficacy, in addition to promoting control of the release and increase in solubility of lipophilic drugs. In view of these aspects, this work aimed at the association of tioconazole with the polymeric nanocapsules of Eudragit® RL 100, glimpsing a new applicability for the drug. The nanocarriers were evaluated in relation to their physical-chemical properties, such as average particle size, zeta potential, polydispersion index, pH, drug content and encapsulation efficiency, besides stability. The release profile, bioadhesive and irritant potential in vitro, as well as the ex vivo eye permeation capacity of the drug were also verified. Additionally, the antifungal activity of nanocarriers was evaluated by means of a cell death curve, in addition to cytotoxicity studies in human mononucleated cells. Colloidal systems remained in the nanometric range (about 140 nm), polydispersion index below 0.17; potential zeta positive and pH in the slightly acid range. The tioconazole content was 2.81 μg/mL and the encapsulation efficiency was close to 100%. The stability of the formulations was maintained during the 60 days of analysis. The nanocapsules containing the drug demonstrated control of tioconazole release and permeation capacity through the cornea, with the presence of nanoparticles on the corneal surface, visualized by microscopy. The suspensions of nanocapsules proved to be less irritating to the eye, when compared to the solution of the non-associated drug, in the same concentration. As for toxicity, the formulations have demonstrated their safety, with decreased cell viability (35.4%) occurring only at the highest concentration of tioconazole (20 μg/mL). However, no oxidative and nitrosative species were generated for any of the concentrations and samples tested. Thus, the formulations developed were considered safe and without signs of cytotoxicity. In addition, in vitro antifungal activity of the nanocapsules containing tioconazole against Candida albicans yeast has been confirmed. The results obtained suggest that the association of tioconazole with Eudragit® RL 100 polymeric nanocapsules is a promising alternative for ocular application in the treatment of fungal keratitis.